Genome-Wide Search for SNP Interactions in GWAS Data: Algorithm, Feasibility, Replication Using Schizophrenia Datasets - Lee, Kwan-Yeung; Leung, Kwong-Sak; Ma, Suk Ling; So, Hon Cheong; Huang, Dan; Tang, Nelson Leung-Sang; Wong, Man-Hon (Frontiers in Genetics, 2020)
In this study, we look for potential gene-gene interaction in susceptibility to schizophrenia by an exhaustive searching for SNP-SNP interactions in 3 GWAS datasets (phs000021:phg000013, phs000021:phg000014, phs000167) using our recently published algorithm. The search space for SNP-SNP interaction is confined to 8 biologically plausible ways of interaction under dominant-dominant or recessive-recessive modes. First, we have performed our search of all pair-wise combination of 729,454 SNPs after filtering by SNP genotype quality. All possible pairwise interactions of any 2 SNPs (5 x 10^-11) were exhausted to search for significant interaction which was defined by p value of chi-square tests. 9 out the top 10 interactions, protein coding genes were partnered with non-coding RNA (lncRNA) which suggested a new alternative insight into interaction biology other than the frequently sought-after protein-protein interaction. Therefore, we extended to look for replication among the top 10,000 interaction SNP pairs and high proportion of concurrent genes forming the interaction pairs were found. The results indicated that a enrichment of signals over noise was present in the top 10,000 interactions. Then, replications of SNP-SNP interaction were confirmed for 9 SNPs-pairs in both replication datasets. Potential binging was discerned for the pair of FHIT (protein coding) and LINC00969 (lncRNA). Both of them were reported to have expression in brain or expression quantitative trait loci (eQTL). Our study represents an early attempt of exhaustive interaction analysis of GWAS data which also yield replicated interaction and new insight into understanding of genetic interaction in schizophrenia.